2020
DOI: 10.21203/rs.3.rs-24572/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-Space Flowering and Podding Characterization in Erect-growing Summer Mung Bean(Vigna radiate L.)

Abstract: The flowering and podding sequences and patterns in different Mung bean varieties were studied by examining the flowering and podding of Xilv 1 and Anlv 7, in order to provide a basis for Mung bean hybridization and high efficiency production. It was shown that the flower period of Mung bean could be divided into initial, full bloom, final stages, and secondary full bloom and final stages. Flowers mainly distributed at nodes 6-8 at the initial flowering stage; distributed at all plant nodes, especially at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…During this period, resources are directed from vegetative to reproductive organs such as flowers and pods (Cohen, 1976). Mungbean typically has an indeterminant growth habit as accumulation of vegetative biomass (both root and shoot) and development of flowers and pods occurs simultaneously (Fakir et al, 2011; Wang et al, 2020). Recent research on Australian mungbean cultivars demonstrated that canopy development ceases at the mid‐pod fill stage when pods transition to be the dominant sinks (Geetika, Collins, et al, 2022), highlighting the importance of source‐sink dynamics in yield development (Smith et al, 2018).…”
Section: Mungbean Developmentmentioning
confidence: 99%
“…During this period, resources are directed from vegetative to reproductive organs such as flowers and pods (Cohen, 1976). Mungbean typically has an indeterminant growth habit as accumulation of vegetative biomass (both root and shoot) and development of flowers and pods occurs simultaneously (Fakir et al, 2011; Wang et al, 2020). Recent research on Australian mungbean cultivars demonstrated that canopy development ceases at the mid‐pod fill stage when pods transition to be the dominant sinks (Geetika, Collins, et al, 2022), highlighting the importance of source‐sink dynamics in yield development (Smith et al, 2018).…”
Section: Mungbean Developmentmentioning
confidence: 99%
“…The vascular defects of dpy1 mutants probably contribute to its drought-sensitive phenotype, which deserves further study. The LRR-RLK FLORAL ORGAN NUMBER1 (FON1) promotes plant drought resistance and represses seed germination in rice via upregulating ABA-responsive genes (Feng et al, 2014). The LRR-RLK could be positive or negative regulators of drought resistance.…”
Section: Formation Of Plasma Membrane Nanodomains Under Osmotic Stressmentioning
confidence: 99%
“…This illness is predominantly recognized by the degree of hyperglycemia that raises the risk of microvascular injury (retinopathy, nephropathy, and neuropathy) (10). It is related to a reduced life expectancy, significant injury from certain diabetes-related microvascular illnesses, an increased risk of macrovascular consequences (peripheral vascular disease, ischemic heart disease, and stroke), and a worse quality of life (11). There are several pathogenetic mechanisms that result in the development of diabetes.…”
Section: Introductionmentioning
confidence: 99%